2013
DOI: 10.1177/0146167213490031
|View full text |Cite
|
Sign up to set email alerts
|

Does Power Help or Hurt? The Moderating Role of Self–Other Focus on Power and Perspective-Taking in Romantic Relationships

Abstract: Reconciling competing viewpoints suggesting that power helps and hurts perspective-taking in close relationships, in two experiments and two daily experience studies we tested the hypothesis that power's effect on perspective-taking depends on the extent to which people are relatively self-versus other-focused. In Study 1, recalling a time of high (vs. low) power over a romantic partner reduced inclinations to take the partner's perspective for relatively self-focused but not other-focused individuals. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 51 publications
1
79
1
Order By: Relevance
“…In general, people who perceive that they are more committed than is their partner will feel underpowered; they may expend a lot of effort in trying to understand their partner's perspective (Gordon & Chen, 2013). In attachment contexts, individuals who are experiencing anxious thoughts and feelings carefully monitor situations for signs of their partner's commitment, readily perceive relationship threats, overreact to daily interactions by reevaluating their relationship, desire more security when they think of trust, and exhibit more negative affect and behavior relative to less anxious individuals (Bartz & Lydon, 2006;Campbell, Simpson, Boldry, & Kashy, 2005;Collins, 1996;Collins, Ford, Guichard, & Allard, 2006;Gere, MacDonald, Joel, Spielmann, & Impett, 2013;Mikulincer, 1998;Pierce & Lydon, 1998;Simpson et al, 1996;Snapp, Lento, Ryu, Rosen, 2014).…”
Section: Attachment Security Enhancement Model 20mentioning
confidence: 99%
“…In general, people who perceive that they are more committed than is their partner will feel underpowered; they may expend a lot of effort in trying to understand their partner's perspective (Gordon & Chen, 2013). In attachment contexts, individuals who are experiencing anxious thoughts and feelings carefully monitor situations for signs of their partner's commitment, readily perceive relationship threats, overreact to daily interactions by reevaluating their relationship, desire more security when they think of trust, and exhibit more negative affect and behavior relative to less anxious individuals (Bartz & Lydon, 2006;Campbell, Simpson, Boldry, & Kashy, 2005;Collins, 1996;Collins, Ford, Guichard, & Allard, 2006;Gere, MacDonald, Joel, Spielmann, & Impett, 2013;Mikulincer, 1998;Pierce & Lydon, 1998;Simpson et al, 1996;Snapp, Lento, Ryu, Rosen, 2014).…”
Section: Attachment Security Enhancement Model 20mentioning
confidence: 99%
“…Similarly, a higher moral identity (i.e., the extent to which moral values are central to the self-concept) generally makes individuals less likely to engage in actions that benefit the self at others' expense, but this effect is even stronger for individuals with power [24]. Within romantic relationships, partners who are more self-focused display more impoverished perspective-taking only when they are the more powerful partner in the relationship [25]. By contrast, when individuals have a strong goal to maintain a relationship (i.e., are strongly committed to it), having more power makes them more likely to forgive their partner when that person transgresses against them [26].…”
Section: Interpersonal Consequences Of Power and Status Differentialsmentioning
confidence: 99%
“…Similarly, Schmid Mast, Jonas, and Hall (2009) reported that the experience of power enhances perspective-taking among empathetic leaders but not among egoistic ones. Along the same lines, Côté and colleagues (2011) found that power amplifies the association between dispositional tendencies and perspective-taking with strangers (see also Gordon and Chen [2013]). …”
Section: Imprinting and Influencementioning
confidence: 88%